Kompetensi Penyuluh Agama Islam dalam Memelihara Harmoni Kerukunan Umat Beragama di Jakarta Selatan - Siti Mukzizatin (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
[COMPETENCY OF ISLAMIC RELIGIOUS INSTRUCTORS IN MAINTAINING HARMONY IN RELIGIOUS COMMUNITIES IN SOUTH JAKARTA] This study aims to determine the Competency of Islamic Religious Instructors in maintaining harmony in Religious Communities in South Jakarta. This study is field research using descriptive analytical methods and qualitative approaches take locus in the South Jakarta area. The Data was collected through interviews and surveys in the form of questionnaires to religious instructors in South Jakarta. The data is processed by inductive analysis, which uses the logic of thinking in which syllogism is built based on specific things and leads to general conclusions. The results showed: (1) The competence of Islamic religious instructors in the South Jakarta region already had the right perception and understanding in building insight (world view) on plurality and multi-ethnicity (multicultural) as well as proactive attitudes and cooperation when managing conflicts by utilizing local wisdom and minimizing differences. (2) Intolerance in Jakarta in many surveys becomes a challenge for religious instructors in building social relations with fostered groups so that the interpretation of religious texts that lead to truth claims considers themselves to be the most correct can be minimized. (3) Continuous guidance and counseling, and periodic interfaith dialogue become social capital to find common ground and solutions for potential conflicts or violence between religious communities or internal religious communities